Vapor growth and interfacial carrier dynamics of high-quality CdS-CdSSe-CdS axial nanowire heterostructures. (February 2017) - Zhang, Qinglin; Liu, Huawei; Guo, Pengfei; Li, Dan; Fan, Peng; Zheng, Weihao; Zhu, Xiaoli; Jiang, Ying; Zhou, Hong; Hu, Wei; Zhuang, Xiujuan; Liu, Hongjun; et al.
Abstract: Well understanding the interfacial carrier dynamics in semiconductor axial nanowire (NW) heterostructures is crucial important for the performance optimization of integrated photonics and optoelectronics devices. However, the growth of high-quality semiconductor axial NW heterostructures still remains a great challenge. Here, we develop a source switching vapor growth route and demonstrate the successful growth of CdS-CdSSe-CdS axial NW heterostructures with highly crystallized and composition sharp interface, which acts as the model material for the study of interfacial carrier dynamics. Under femtosecond laser pumping, the achieved NW heterostructures can simultaneously give lasing at the green (~516.4 nm) and red (~597.9 nm) spectral regions, demonstrating the well radial confinement of the both color emitted light. Time-resolved photoluminescence (PL) measurements reveal the energy transfer (ET) from the CdS to the CdSSe segments corresponds to the interaction of the guided green light with CdSSe at the hetero-interfaces, which makes the CdSSe segment have higher carrier density and emission efficiency, resulting in the more obvious power induced blueshift and lower lasing threshold comparing with the green emission. These obtained CdS-CdSSe-CdS axial NW heterostructures with effective ET have the potential applications in high performance optical and optoelectronic nanoscaled devices, like nanolaser, photodetectors, waveguide etc. Graphical abstract: We realize the controlled growth of CdS-CdSSe-CdS axial nanowire heterostructures with highly crystallized and composition sharp interface. Optically pumped dual-wavelength lasing is demonstrated at room temperature based on these unique nanowire heterostructures. Time-resolved PL measurements reveal the energy transfer from the CdS segment to the CdSSe segment, which plays important roles on the lasing activity of the heterostructures. Highlights: CdS-CdSSe-CdS axial nanowire heterostructures with highly crystallized and composition sharp interface are grown with a source switching vapor growth route. Green (~516.4 nm) and red (~597.9 nm) color lasing are realized with the threshold of the red lower than that of the green one, which indicates the individual wires are good waveguide and resonant cavity. Time-resolved photoluminescence characterizations reveal Energy transfer from the CdS to the CdSSe segments, corresponding to the interaction of the guided green light with CdSSe at the hetero-interfaces.